PENGEMBANGAN KAJIAN MATAN HADIS DENGAN MENGGUNAKAN PENDEKATAN ILMU-ILMU SOSIAL - Risqo Faridatul Ulya, Udi Yuliarto (Ushuluddin Faculty, PTIQ Institute, 2022)
This paper discusses the development and study of attention using a social science approach. This research is literature research with a literature review and uses the analysis-descriptive method. The purpose of this paper is to reveal that the development of observational studies using the social sciences approach is indispensable in studying. The study of hadith observations through a social science approach is a method or way of understanding a hadith text or hadith content with the help of other social science disciplines. The social sciences include sociology, anthropology, psychology, economics, social geography, politics, and history. With the aim of making it easier for readers to understand the text or content in the hadith's own eyes.